Strategic Pathways for Developing Cassava-Based Agroindustry within Local Agrifood Systems - Yunianti; Nurhapsa; Suherman (Edupedia Publisher, 2025)
Cassava-based agroindustry plays a strategic role in strengthening local agrifood systems by connecting agricultural production, food processing, and local markets. However, many small-scale cassava processing enterprises operate under structural constraints that limit their contribution to sustainable agrifood system development. This study examines strategic pathways for developing cassava-based agroindustry by analyzing internal and external factors that shape enterprise performance within a local agrifood system. A qualitative–quantitative approach using SWOT analysis was applied, drawing on field observations, interviews with agroindustry actors, and secondary data. The results show that stable access to local cassava, processing experience, and product acceptance constitute key internal strengths; limited production capacity, simple technology, and narrow market reach remain major constraints. Externally, increasing demand for local food products and institutional support create development opportunities, whereas competition and market volatility pose persistent challenges. The resulting strategic pathways emphasize value upgrading, gradual innovation, enterprise resilience, and operational stability. Overall, the findings indicate that context-sensitive and system-oriented strategies are essential for enhancing the sustainability of cassava-based agroindustry and reinforcing the integration and resilience of local agrifood systems.